2007
DOI: 10.3949/ccjm.74.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and minimizing late thrombosis of drug-eluting stents.

Abstract: Although the safety profiles of drug-eluting stents are similar to those of bare metal stents in the short term, concern has arisen about their potential for late thrombosis (occurring > 30 days after implantation). Stent thrombosis is rare but potentially devastating and can result in ST-segment elevation myocardial infarction or death. The aim of this article is to review the incidence, predictors, pathology, and prevention of late thrombosis of drug-eluting stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Although the DES reduced the restenosis rate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) by preventing smooth muscle cell proliferation, it increased the rate of stent thrombosis (1,(25)(26)(27)(28) after 1 year (very late stent thrombosis), a result rarely seen in BMS. Late stent thrombosis may be caused by the poorly formed neointima over DES that has failed to cover and stabilize underlying thrombogenic yellow plaque.…”
Section: Atherosclerotic Neointima Over Desmentioning
confidence: 99%
“…Although the DES reduced the restenosis rate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) by preventing smooth muscle cell proliferation, it increased the rate of stent thrombosis (1,(25)(26)(27)(28) after 1 year (very late stent thrombosis), a result rarely seen in BMS. Late stent thrombosis may be caused by the poorly formed neointima over DES that has failed to cover and stabilize underlying thrombogenic yellow plaque.…”
Section: Atherosclerotic Neointima Over Desmentioning
confidence: 99%
“…Because there is uncertainty about whether to continue clopidogrel indefinitely in the case of DES, further randomized trials are required [41]. Until such data are accrued, our practice has been to continue dual antiplatelet therapy indefinitely, assuming that the patient does not have any major bleeding problems during the first year of therapy [42].…”
Section: Clopidogrel and Stent Thrombosismentioning
confidence: 99%
“…[34][35][36][37] Late stent thrombosis is a rare complication of stenting and, even in studies that have indicated an increased risk with DES, the absolute risk remains low (,1.5%). 34,37 However, it is also a serious complication, resulting in MI in 60-70% of cases and mortality rates of nearly 50%, 38,39 and so any increase in the rate of late stent thrombosis is a cause for concern.…”
Section: Drug-eluting Stents: the Risksmentioning
confidence: 99%